Teaching classics with technology - Natoli, Bartolo; Hunt, Steven (Classicist) (London ; New York : Bloomsbury Academic, 2019)
"The impact of ICT on the teaching of classical languages, literature and culture has not until now been extensively described and evaluated. Nevertheless, educational technology has made a huge difference to the ways in which Classics is taught at junior, senior and college level. The book brings together ten major approaches to the use of technology in the classroom and presents them for a wide, international audience. It thus forms a record of current and developing practice, promotes further discussion and use among practitioners (teachers, learners and trainers) and offers suggestions for changes in pedagogical practices in the teaching of Classics for the better. The many examples of practice from both UK and US perspectives are applicable to countries throughout the world where Classics is being taught. The more traditional curricula of high-school education in the UK and Europe are drawing more and more on edutech, whereas educational jurisdictions in the US are increasingly expecting high-school students to use ICT in all lessons, with some actively dissuading schools from using traditional printed textbooks. This book presents US teachers with a vital resource as they adapt to this use of educational technology in Classics teaching. This is no less pertinent at university level, in the UK and US, where pedagogy tends to follow traditionalist paradigms: this book offers lecturers frameworks for understanding and assimilating the models of teaching and learning which are prevalent in schools and experienced by their students"--
Flipping Romans : experiments in using technology for teaching in higher education / Kate Gilliver -- Auream quisquis mediocritatem diligit : the joyful learning community model for learning Latin online / Justin Schwamm -- Distance learning Latin / Verity Walden -- Making it count : measuring student engagement with online Latin resources at the Open University / Mair Lloyd and James Robson -- VLW, Latin literature, and student voice / Elizabeth Lewis -- Going digital : the principles behind CyberCaesar / Alan Chadwick -- Una vita : exploring the relationship between play, learning science, and cultural competency / Stephen Slota and Kevin Ballestrini -- Using virtual learning environments for classics outreach / Emma Searle -- From research on Roman history into cartoons and outreach to UK schools / Ray Laurence -- Vase animations and primary-aged learners / Sonya Nevin -- Sketchup and digital modelling for classics / Matthew Nicholls -- iPad technology and the classics classroom / Caron Downes -- Just-in-time learning : using handheld voting devices in the undergraduate lecture room / Helen Lovatt -- Teaching the geography of the ancient world / Scott Arcenas -- Bridging the gap between students and antiquity : language acquisition videos with Minecraft and CI/TPRS / Jessie Craft -- On stage and screen : "big book" Latin and dialogic teaching / Steven Hunt -- Using annotations in Google Docs to foster authentic classics learning / Roger Travis -- Project-based learning, technology, and the advanced language classroom / Bartolo Natoli -- In the classroom with multi-modal teaching / Lisa Hay.
Includes bibliographical references and index.
Keywords: Classical literature -- Study and teaching -- Technological innovations; Classical education -- Technological innovations; Educational technology